InGaN photocatalysts on conductive Ga2O3 substrates. Issue 5 (1st April 2015) - Ogita, Taro; Uetake, Yusuke; Yamashita, Yoshihiro; Kuramata, Akito; Yamakoshi, Shigenobu; Ohkawa, Kazuhiro
<x xml:space="preserve">Abstract</x> We succeeded in hydrogen evolution using InGaN photocatalysts grown on conductive Ga2O3 substrates. These photocatalysts exhibited a conversion efficiency of 0.8% from incident light energy to stored H2 chemical energy. Their quantum efficiency was determined to be more than 1% at 404 nm by incident photon‐to‐current conversion efficiency (IPCE) measurement. We found that the wavelength response of the InGaN structure can be extended to the visible region. These results indicate that the conductive Ga2O3 substrates are suitable for the photocatalysts.